Prevention of Hydrogen Peroxide‐Induced Red Blood Cells Lysis by Ilex paraguariensis Aqueous Extract: Participation of Phenolic and Xanthine Compounds - Peralta, Ignacio Nahuel (2012)
The fresh leaves and stems of Ilex paraguariensis (Aquifoliaceae) are employed to prepare the commercial product used in North-eastern Argentina, Southern Brazil and Eastern Paraguay named mate. The presence of polyphenols and xanthines, which present antioxidant activity, is well described in I. paraguariensis. ROS play an important role in tissue damage and pathological events in living organisms affecting erythrocyte?s membranes inducing to hemolysis. Taking into account, the aim of this work was to evaluate the protective effect of an aqueous extract of I. paraguariensis (green leaves) on the hemolysis of red blood cells (RBC) induced by H2O2 and correlate this activity with the enzymatic like activity related to H2O2 metabolism. The antioxidant activity of chlorogenic acid and caffeine was also analyzed in order to investigate their participation in the activity of the crude extract. The extract as well as the compounds protected RBC from hemolysis in relation to enzymatic CAT like activity. This study could contribute to the knowledge of the antioxidant activity of I. paraguariensis in view of the great quantities of yerba mate consumed by population.